Enhanced ceramic zinc borate nano flame retardant and preparation method thereof

By preparing an enhanced ceramic zinc borate nano flame retardant, the synergistic effect of phosphorus, silicon, and boron elements is utilized to form a dense protective layer, which solves the problem of insufficient flame retardant effect of existing zinc borate flame retardants and achieves a high-efficiency and environmentally friendly improvement in flame retardant performance.

CN119264520AInactive Publication Date: 2025-01-07ZIBO WUWEI INDAL

Patent Information

Application Number
CN202411785747.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of flame retardants, and discloses an enhanced ceramic zinc borate nano flame retardant and a preparation method thereof.The enhanced ceramic zinc borate nano flame retardant is obtained by adding ceramic zinc borate, a sulfur-containing flame retardant and sodium sulfonate modified silane into a stirrer and stirring. The enhanced ceramic zinc borate nano flame retardant is obtained by adding ceramic zinc borate, a sulfur-containing flame retardant and sodium sulfonate modified silane into a stirrer and stirring. Boron elements, sulfur elements, phosphorus elements, silicon elements and sodium sulfonate groups in the sulfur-containing flame retardant and the sodium sulfonate modified silane jointly form a flame-retardant system, and synergistic flame retardance is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flame retardants, in particular to a reinforced ceramic zinc borate nano flame retardant and a preparation method thereof. Background Art

[0002] Zinc borate is a boron-based flame retardant with a chemical composition of xZnOyB2O3zH2O. Zinc borate can be used as a highly efficient flame retardant synergist and is widely used in polyvinyl chloride, polyolefins, elastomers, polyamides, and epoxy resins. How to further improve its flame retardant effect is the key to solving the problem.

[0003] For example, patent CN112062963A discloses an organosilicon silsesquioxane flame retardant and a preparation method thereof. The flame retardant of the invention has very good compatibility and can significantly improve the comprehensive properties of the resin. The catalyst material has good catalytic properties and is easy to separate and reuse, and has the advantages of simple operation and environmental protection, but its flame retardant effect has not been improved. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides an enhanced ceramic zinc borate nano flame retardant and a preparation method thereof, which has good flame retardant effect.

[0005] To achieve the above object, the present invention provides the following technical solution: an enhanced ceramic zinc borate nano flame retardant, comprising the following weight components: 15-20 parts by weight of ceramic zinc borate, 4-6 parts by weight of sulfur-containing flame retardant, and 3-5 parts by weight of sodium sulfonate modified silane.

[0006] Preferably, the preparation method of the sulfur-containing flame retardant is: (1) Adding a boron-containing triamine, an olefin compound derived from vanillin, anhydrous magnesium sulfate and anhydrous ethanol into a reactor, introducing nitrogen protection, reflux reaction for 10-12 hours, and after the reaction, filtering, rotary distillation, and washing with ethyl acetate to obtain a boron-containing triallyl compound; (2) Adding a boron-containing triallyl compound to an N,N-dimethylformamide solvent, stirring and dispersing, and then adding mercaptoethylamine and benzoin dimethyl ether photoinitiators, irradiating with ultraviolet light at 25-40° C. for 3-4 hours, centrifuging, washing and drying to obtain an intermediate 1; (3) Add intermediate 1, 2,6-dialdehyde-1,5-dihydroxynaphthalene to a reactor filled with ethanol solvent, stir evenly, introduce nitrogen protection, react at 40-65°C for 2-4 hours, then continue to add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, continue to react at 50-70°C for 3-5 hours, cool after completion, filter and dry to obtain intermediate 2; (4) Add intermediate 2 and pentaerythritol methyl silicate to N,N-dimethylformamide solvent, stir and mix, continue to add malonyl chloride and triethylamine catalyst, react at 70-100° C. for 5-6 hours, distill under reduced pressure after the reaction, wash and dry to obtain a sulfur-containing flame retardant.

[0007] The boron-containing triamine and an olefinic compound derived from vanillin are reacted to introduce an olefinic group, thereby obtaining a boron-containing triallyl compound; the olefinic group in the boron-containing triallyl compound is reacted with the thiol group in mercaptoethylamine to introduce an amine group, thereby obtaining intermediate 1; the amine group in intermediate 1 and the aldehyde group in 2,6-dialdehyde-1,5-dihydroxynaphthalene are subjected to condensation reaction, and then 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is added thereto to introduce a hydroxyl group, thereby obtaining intermediate 2; intermediate 2 is reacted with the hydroxyl group in pentaerythritol methyl silicate and the acyl chloride group in malonyl chloride, thereby obtaining a sulfur-containing flame retardant.

[0008] Preferably, the mass ratio of the boron triamine, the olefin compound derived from vanillin, and the anhydrous magnesium sulfate in (1) is 1:2.1-2.6:1.2-1.5.

[0009] Preferably, the mass ratio of the boron-containing triallyl compound, mercaptoethylamine, and benzoin dimethyl ether photoinitiator in (2) is 0.8-1.1:1:0.01-0.02.

[0010] Preferably, in the (3), the mass ratio of the intermediate 1, 2,6-dialdehyde-1,5-dihydroxynaphthalene, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 1:1.2-1.4:0.9-1.5.

[0011] Preferably, the mass ratio of the intermediate 2, pentaerythritol methyl silicate, malonyl chloride and triethylamine catalyst in (4) is 1.1-1.3:1.6-2.2:1:0.02-0.03.

[0012] Preferably, the preparation method of the sodium sulfonate modified silane is: S1. Under a nitrogen atmosphere, 4-6 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was added to tetrahydrofuran solvent, stirred to dissolve, and then 0.01-0.03 g of azobisisobutyronitrile initiator and 3.6-4.5 g of di(dimethylamino)methylvinylsilane were added thereto, and the mixture was reacted at 60-85° C. for 10-12 h. After the reaction was completed, the mixture was distilled under reduced pressure and dried in vacuum for 6-8 h to obtain a phosphorus-containing tertiary aminosilane; S2. Add 3.1-3.5 g of phosphorus-containing tertiary amino silane and 4.3-5.7 g of propenyl-1,3-sulfonate to acetone solvent for dissolution, then add 2-5% sodium hydroxide solution, react at 60-90°C for 8-12 hours, concentrate under reduced pressure to remove the solvent after the reaction, filter, and obtain sodium sulfonate modified silane.

[0013] Preferably, the preparation method of the enhanced ceramic zinc borate nano flame retardant is: adding ceramic zinc borate, sulfur-containing flame retardant, and sodium sulfonate modified silane into a stirrer, stirring for 2-4 minutes, to obtain the enhanced ceramic zinc borate nano flame retardant; the size of the nano flame retardant is 40-60nm.

[0014] The invention prepares the enhanced ceramic zinc borate nano flame retardant by adding ceramic zinc borate, sulfur-containing flame retardant and sodium sulfonate modified silane into a stirrer and stirring.

[0015] The boron, sulfur, phosphorus, silicon and sodium sulfonate groups in the sulfur-containing flame retardant and sodium sulfonate modified silane together constitute a flame retardant system with synergistic flame retardancy. The phosphorus contained therein generates acidic substances such as polyphosphoric acid and metaphosphoric acid when heated, which can dehydrate and carbonize the surface of the burning polymer. Since polyphosphoric acid and metaphosphoric acid are not easy to volatilize, they can form a dense protective layer on the surface of the polymer; the silicon contained therein can promote the carbonization process of the material at high temperature, and form a continuous and dense inorganic insulating carbon layer containing silicon and carbon on the surface of the material, thereby achieving the purpose of flame retardancy; the three-dimensional network structure formed by the boron-oxygen bond has high flame retardancy with high oxygen index, low toxicity, low smoke and low calorific value; the sulfur element and sodium sulfonate group therein also have good flame retardant effect. DETAILED DESCRIPTION

[0016] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] The boron triallyl compound reacts as follows:

[0018] The enhanced ceramic zinc borate nano flame retardant obtained by the invention is ball-milled by a ball mill, and the particle size after ball-milling is 40-60nm.

[0019] Embodiment 1: (1) Add 1 g of a boron-containing triamine, 2.1 g of a vanillin-derived olefin compound, 1.2 g of anhydrous magnesium sulfate and 60 ml of anhydrous ethanol into a reactor, introduce nitrogen protection, reflux for 10 h, filter and rotary distill after the reaction, and wash with ethyl acetate to obtain a boron-containing triallyl compound; (2) Add 0.8 g of a boron-containing triallyl compound to 70 ml of N,N-dimethylformamide solvent, stir and disperse, then add 1 g of mercaptoethylamine and 0.01 g of benzoin dimethyl ether photoinitiator, irradiate with ultraviolet light at 25°C for 3 h, centrifuge, wash and dry to obtain intermediate 1; (3) 1 g of intermediate 1 and 1.2 g of 2,6-dialdehyde-1,5-dihydroxynaphthalene were added to a reactor containing 75 ml of ethanol solvent, stirred evenly, and nitrogen was introduced for protection. The mixture was reacted at 40°C for 2 h, and then 0.9 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was added thereto. The reaction was continued at 50°C for 3 h. After the reaction was completed, the mixture was cooled, filtered and dried to obtain intermediate 2; (4) Add 1.1 g of intermediate 2 and 1.6 g of pentaerythritol methyl silicate to 60 ml of N,N-dimethylformamide solvent, stir and mix, then add 1 g of malonyl chloride and 0.02 g of triethylamine catalyst, react at 70 °C for 5 h, distill under reduced pressure after the reaction, wash and dry to obtain a sulfur-containing flame retardant; (5) Under nitrogen atmosphere, add 4 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to 50 ml of tetrahydrofuran solvent, stir and dissolve, then add 0.01 g of azobisisobutyronitrile initiator and 3.6 g of di(dimethylamino)methylvinylsilane, react at 60° C. for 10 h. After the reaction is completed, distill under reduced pressure and vacuum dry for 6 h to obtain phosphorus-containing tertiary aminosilane; (6) Add 3.1 g of phosphorus-containing tertiary amino silane and 4.3 g of propenyl-1,3-sultone to 70 ml of acetone solvent for dissolution, then add 2 ml of 2% sodium hydroxide solution, react at 60° C. for 8 h, concentrate under reduced pressure to remove the solvent, and filter to obtain sodium sulfonate modified silane; (7) 15 parts by weight of ceramic zinc borate, 4 parts by weight of sulfur-containing flame retardant, and 3 parts by weight of sodium sulfonate modified silane were added into a stirrer and stirred for 2 minutes to obtain an enhanced ceramic zinc borate nano flame retardant; the size of the nano flame retardant was 40 nm.

[0020] Embodiment 2: (1) Add 1 g of boron-containing triamine, 2.6 g of vanillin-derived olefin compound, 1.5 g of anhydrous magnesium sulfate and 95 ml of anhydrous ethanol into a reactor, introduce nitrogen protection, reflux for 12 h, filter and rotary distill after the reaction, and wash with ethyl acetate to obtain a boron-containing triallyl compound; (2) Add 1.1 g of a boron-containing triallyl compound to 90 ml of N,N-dimethylformamide solvent, stir and disperse, then add 1 g of mercaptoethylamine and 0.02 g of benzoin dimethyl ether photoinitiator, irradiate with ultraviolet light at 40°C for 4 h, centrifuge, wash and dry to obtain intermediate 1; (3) Add 2 g of intermediate 1 and 2.8 g of 2,6-dialdehyde-1,5-dihydroxynaphthalene into a reactor containing 100 ml of ethanol solvent, stir evenly, introduce nitrogen protection, react at 65°C for 4 h, then continue to add 3 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, continue to react at 70°C for 5 h, cool after completion, filter and dry to obtain intermediate 2; (4) Add 1.3 g of intermediate 2 and 2.2 g of pentaerythritol methyl silicate to 80 ml of N,N-dimethylformamide solvent, stir and mix, then add 1 g of malonyl chloride and 0.03 g of triethylamine catalyst, react at 100 °C for 6 h, distill under reduced pressure after the reaction, wash and dry to obtain a sulfur-containing flame retardant; (5) Under nitrogen atmosphere, add 6 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to 95 ml of tetrahydrofuran solvent, stir and dissolve, then add 0.03 g of azobisisobutyronitrile initiator and 4.5 g of di(dimethylamino)methylvinylsilane, react at 85° C. for 12 h. After the reaction is completed, distill under reduced pressure and vacuum dry for 8 h to obtain phosphorus-containing tertiary aminosilane; (6) Add 3.5 g of phosphorus-containing tertiary amino silane and 5.7 g of propenyl-1,3-sultone to 90 ml of acetone solvent for dissolution, then add 4 ml of 5% sodium hydroxide solution, react at 90° C. for 12 h, concentrate under reduced pressure to remove the solvent, and filter to obtain sodium sulfonate modified silane; (7) 20 parts by weight of ceramic zinc borate, 6 parts by weight of sulfur-containing flame retardant, and 5 parts by weight of sodium sulfonate modified silane were added into a stirrer and stirred for 4 minutes to obtain an enhanced ceramic zinc borate nano flame retardant; the size of the nano flame retardant was 60 nm.

[0021] Embodiment three: (1) Add 1 g of a boron-containing triamine, 2.4 g of a vanillin-derived olefin compound, 1.3 g of anhydrous magnesium sulfate and 75 ml of anhydrous ethanol into a reactor, introduce nitrogen protection, reflux for 11 h, filter and rotary distill after the reaction, and wash with ethyl acetate to obtain a boron-containing triallyl compound; (2) Add 0.9 g of a boron-containing triallyl compound to 80 ml of N,N-dimethylformamide solvent, stir and disperse, then add 1 g of mercaptoethylamine and 0.01 g of benzoin dimethyl ether photoinitiator, irradiate with ultraviolet light at 30° C. for 3 h, centrifuge, wash and dry to obtain intermediate 1; (3) 1 g of intermediate 1 and 2.2 g of 2,6-dialdehyde-1,5-dihydroxynaphthalene were added to a reactor containing 85 ml of ethanol solvent, stirred evenly, and nitrogen was introduced for protection. The mixture was reacted at 50°C for 3 h, and then 2.4 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was added thereto. The reaction was continued at 60°C for 4 h. After the reaction was completed, the mixture was cooled, filtered and dried to obtain intermediate 2; (4) Add 1.2 g of intermediate 2 and 1.8 g of pentaerythritol methyl silicate to 70 ml of N,N-dimethylformamide solvent, stir and mix, then add 1 g of malonyl chloride and 0.02 g of triethylamine catalyst, react at 80° C. for 5 h, distill under reduced pressure after the reaction, wash and dry to obtain a sulfur-containing flame retardant; (5) Under nitrogen atmosphere, add 5 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to 85 ml of tetrahydrofuran solvent, stir and dissolve, then add 0.01 g of azobisisobutyronitrile initiator and 4.1 g of di(dimethylamino)methylvinylsilane, react at 75°C for 11 h. After the reaction is completed, distill under reduced pressure and vacuum dry for 7 h to obtain phosphorus-containing tertiary aminosilane; (6) Add 3.2 g of phosphorus-containing tertiary amino silane and 5.2 g of propenyl-1,3-sultone to 80 ml of acetone solvent for dissolution, then add 3 ml of 4% sodium hydroxide solution, react at 70° C. for 8 h, concentrate under reduced pressure to remove the solvent, and filter to obtain sodium sulfonate modified silane; (7) 18 parts by weight of ceramic zinc borate, 5 parts by weight of sulfur-containing flame retardant, and 4 parts by weight of sodium sulfonate modified silane were added into a stirrer and stirred for 3 minutes to obtain a reinforced ceramic zinc borate nano flame retardant; the size of the nano flame retardant was 50 nm.

[0022] Embodiment 4: (1) Add 1 g of a boron-containing triamine, 2.1 g of a vanillin-derived olefin compound, 1.2 g of anhydrous magnesium sulfate and 60 ml of anhydrous ethanol into a reactor, introduce nitrogen protection, reflux for 10 h, filter and rotary distill after the reaction, and wash with ethyl acetate to obtain a boron-containing triallyl compound; (2) Add 0.8 g of a boron-containing triallyl compound to 70 ml of N,N-dimethylformamide solvent, stir and disperse, then add 1 g of mercaptoethylamine and 0.01 g of benzoin dimethyl ether photoinitiator, irradiate with ultraviolet light at 25°C for 3 h, centrifuge, wash and dry to obtain intermediate 1; (3) Add 2 g of intermediate 1 and 2.8 g of 2,6-dialdehyde-1,5-dihydroxynaphthalene into a reactor containing 100 ml of ethanol solvent, stir evenly, introduce nitrogen protection, react at 65°C for 4 h, then continue to add 3 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, continue to react at 70°C for 5 h, cool after completion, filter and dry to obtain intermediate 2; (4) Add 1.3 g of intermediate 2 and 2.2 g of pentaerythritol methyl silicate to 80 ml of N,N-dimethylformamide solvent, stir and mix, then add 1 g of malonyl chloride and 0.03 g of triethylamine catalyst, react at 100 °C for 6 h, distill under reduced pressure after the reaction, wash and dry to obtain a sulfur-containing flame retardant; (5) Under nitrogen atmosphere, add 5 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to 85 ml of tetrahydrofuran solvent, stir and dissolve, then add 0.01 g of azobisisobutyronitrile initiator and 4.1 g of di(dimethylamino)methylvinylsilane, react at 75°C for 11 h. After the reaction is completed, distill under reduced pressure and vacuum dry for 7 h to obtain phosphorus-containing tertiary aminosilane; (6) Add 3.2 g of phosphorus-containing tertiary amino silane and 5.2 g of propenyl-1,3-sultone to 80 ml of acetone solvent for dissolution, then add 2 ml of 4% sodium hydroxide solution, react at 70° C. for 8 h, concentrate under reduced pressure to remove the solvent, and filter to obtain sodium sulfonate modified silane; (7) 18 parts by weight of ceramic zinc borate, 5 parts by weight of sulfur-containing flame retardant, and 4 parts by weight of sodium sulfonate modified silane were added into a stirrer and stirred for 3 minutes to obtain an enhanced ceramic zinc borate nano flame retardant; the size of the nano flame retardant was 45 nm.

[0023] Embodiment five: (1) Add 1 g of boron-containing triamine, 2.6 g of vanillin-derived olefin compound, 1.5 g of anhydrous magnesium sulfate and 95 ml of anhydrous ethanol into a reactor, introduce nitrogen protection, reflux for 12 h, filter and rotary distill after the reaction, and wash with ethyl acetate to obtain a boron-containing triallyl compound; (2) Add 1.1 g of a boron-containing triallyl compound to 90 ml of N,N-dimethylformamide solvent, stir and disperse, then add 1 g of mercaptoethylamine and 0.02 g of benzoin dimethyl ether photoinitiator, irradiate with ultraviolet light at 40°C for 4 h, centrifuge, wash and dry to obtain intermediate 1; (3) 1 g of intermediate 1 and 2.2 g of 2,6-dialdehyde-1,5-dihydroxynaphthalene were added to a reactor containing 85 ml of ethanol solvent, stirred evenly, and nitrogen was introduced for protection. The mixture was reacted at 50°C for 3 h, and then 2.4 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was added thereto. The reaction was continued at 60°C for 4 h. After the reaction was completed, the mixture was cooled, filtered and dried to obtain intermediate 2; (4) Add 1.2 g of intermediate 2 and 1.8 g of pentaerythritol methyl silicate to 70 ml of N,N-dimethylformamide solvent, stir and mix, then add 1 g of malonyl chloride and 0.02 g of triethylamine catalyst, react at 80° C. for 5 h, distill under reduced pressure after the reaction, wash and dry to obtain a sulfur-containing flame retardant; (4) Add 1.1 g of intermediate 2 and 1.6 g of pentaerythritol methyl silicate to 60 ml of N,N-dimethylformamide solvent, stir and mix, then add 1 g of malonyl chloride and 0.02 g of triethylamine catalyst, react at 70 °C for 5 h, distill under reduced pressure after the reaction, wash and dry to obtain a sulfur-containing flame retardant; (5) Under nitrogen atmosphere, add 4 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to 50 ml of tetrahydrofuran solvent, stir and dissolve, then add 0.01 g of azobisisobutyronitrile initiator and 3.6 g of di(dimethylamino)methylvinylsilane, react at 60° C. for 10 h. After the reaction is completed, distill under reduced pressure and vacuum dry for 6 h to obtain phosphorus-containing tertiary aminosilane; (6) Add 3.1 g of phosphorus-containing tertiary amino silane and 4.3 g of propenyl-1,3-sultone to 70 ml of acetone solvent for dissolution, then add 3 ml of 2% sodium hydroxide solution, react at 60° C. for 8 h, concentrate under reduced pressure to remove the solvent, and filter to obtain sodium sulfonate modified silane; (7) Add 15 parts by weight of ceramic zinc borate, 4 parts by weight of sulfur-containing flame retardant, and 3 parts by weight of sodium sulfonate modified silane into a stirrer and stir for 2 minutes to obtain a reinforced ceramic zinc borate nano flame retardant; the size of the nano flame retardant is 50 nm.

[0024] Comparative Example 1 The difference between this comparative example and Example 5 is that pentaerythritol methyl silicate is used instead of the sulfur-containing flame retardant.

[0025] Comparative Example 2 The difference between this comparative example and Example 5 is that 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is used instead of sodium sulfonate modified silane.

[0026] Comparative Example 3 The difference between this comparative example and Example 5 is that pentaerythritol methyl silicate is used instead of the sulfur-containing flame retardant, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is used instead of sodium sulfonate modified silane.

[0027] The limiting oxygen index of the flame retardant was tested using an oxygen index meter, and the combustion grade of the flame retardant was tested using a horizontal and vertical combustion instrument. The test results are shown in Table 1.

[0028] Table 1: Flame retardancy tests.

[0029]

[0030] It can be seen from Table 1 that Examples 1-5 of the present invention have better flame retardant effects than Comparative Examples 1-3.

[0031] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0032] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. An enhanced ceramic zinc borate nano flame retardant, characterized in that: The invention comprises the following components by weight: 15-20 parts by weight of ceramic zinc borate, 4-6 parts by weight of sulfur-containing flame retardant and 3-5 parts by weight of sodium sulfonate modified silane.

2. The enhanced ceramic zinc borate nano flame retardant according to claim 1, characterized in that: The preparation method of the sulfur-containing flame retardant is: (1) Adding a boron-containing triamine, an olefin compound derived from vanillin, anhydrous magnesium sulfate and anhydrous ethanol into a reactor, introducing nitrogen protection, reflux reaction for 10-12 hours, and after the reaction, filtering, rotary distillation, and washing with ethyl acetate to obtain a boron-containing triallyl compound; (2) Adding a boron-containing triallyl compound to an N,N-dimethylformamide solvent, stirring and dispersing, and then adding mercaptoethylamine and benzoin dimethyl ether photoinitiators, irradiating with ultraviolet light at 25-40° C. for 3-4 hours, centrifuging, washing and drying to obtain an intermediate 1; (3) Add intermediate 1, 2,6-dialdehyde-1,5-dihydroxynaphthalene to a reactor filled with ethanol solvent, stir evenly, introduce nitrogen protection, react at 40-65°C for 2-4 hours, then continue to add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, continue to react at 50-70°C for 3-5 hours, cool after completion, filter and dry to obtain intermediate 2; (4) Add intermediate 2 and pentaerythritol methyl silicate to N,N-dimethylformamide solvent, stir and mix, continue to add malonyl chloride and triethylamine catalyst, react at 70-100° C. for 5-6 hours, distill under reduced pressure after the reaction, wash and dry to obtain a sulfur-containing flame retardant.

3. The enhanced ceramic zinc borate nano flame retardant according to claim 2, characterized in that: The mass ratio of the boron triamine, the olefin compound derived from vanillin, and the anhydrous magnesium sulfate in (1) is 1:2.1-2.6:1.2-1.

5.

4. The enhanced ceramic zinc borate nano flame retardant according to claim 2, characterized in that: The mass ratio of the boron triallyl compound, mercaptoethylamine and benzoin dimethyl ether photoinitiator in (2) is 0.8-1.1:1:0.01-0.

02.

5. The enhanced ceramic zinc borate nano flame retardant according to claim 2, characterized in that: The mass ratio of the intermediate 1, 2,6-dialdehyde-1,5-dihydroxynaphthalene and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in (3) is 1:1.2-1.4:0.9-1.

5.

6. The enhanced ceramic zinc borate nano flame retardant according to claim 2, characterized in that: The mass ratio of the intermediate 2, pentaerythritol methyl silicate, malonyl chloride and triethylamine catalyst in (4) is 1.1-1.3:1.6-2.2:1:0.02-0.

03.

7. The enhanced ceramic zinc borate nano flame retardant according to claim 1, characterized in that: The preparation method of the sodium sulfonate modified silane is: S1. Under a nitrogen atmosphere, 4-6 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was added to tetrahydrofuran solvent, stirred to dissolve, and then 0.01-0.03 g of azobisisobutyronitrile initiator and 3.6-4.5 g of di(dimethylamino)methylvinylsilane were added thereto, and the mixture was reacted at 60-85° C. for 10-12 h. After the reaction was completed, the mixture was distilled under reduced pressure and dried in vacuum for 6-8 h to obtain a phosphorus-containing tertiary aminosilane; S2. Add 3.1-3.5 g of phosphorus-containing tertiary amino silane and 4.3-5.7 g of propenyl-1,3-sulfonate to acetone solvent for dissolution, then add 2-5% sodium hydroxide solution, react at 60-90°C for 8-12 hours, concentrate under reduced pressure to remove the solvent after the reaction, filter, and obtain sodium sulfonate modified silane.

8. A method for preparing the enhanced ceramic zinc borate nano flame retardant according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: adding ceramic zinc borate, sulfur-containing flame retardant and sodium sulfonate modified silane into a stirrer, stirring for 2-4 minutes, and obtaining an enhanced ceramic zinc borate nano flame retardant.

Citation Information

Patent Citations

  • Triazine triphenyl phosphinic acid methyl ester flame retardant composition and application method thereof

    CN104231311A

  • Silane modified flame-retardant cable and preparation method thereof

    CN106084561A

  • Vitrified low-smoke halogen-free flame-retardant cable material

    CN109054267A

  • Sulfur-silicon synergistic multi-element flame retardant and preparation method thereof

    CN118406083A

  • Flame retardant resin composition

    US20070173572A1

Cited By

  • Flame-retardant liquid and preparation method thereof

    CN119709009A

  • Preparation process of ceramic zinc borate flame retardant

    CN120699328A

  • PVC automobile film and preparation method thereof

    CN121182098A

  • Chip packaging insulating material and preparation method thereof

    CN121825177A

  • A chip packaging insulating material and its preparation method

    CN121825177B